Commercial insurance delays direct‐acting antiviral treatment for hepatitis C kidney transplantation into uninfected recipients. Issue 1 (3rd September 2020) - Torabi, Julia; Rocca, Juan P.; Ajaimy, Maria; Melvin, Jeffrey; Campbell, Alesa; Akalin, Enver; Liriano, Luz E.; Azzi, Yorg; Pynadath, Cindy; Greenstein, Stuart M.; Le, Marie; Goldstein, Doctor Y.; et al.
Abstract: Introduction: The advent of direct‐acting antivirals (DAAs) has created an avenue for transplantation of hepatitis C virus (HCV)‐infected donors into uninfected recipients (D+/R−). The donor transmission of HCV is then countered by DAA administration during the post‐operative period. However, initiation of DAA treatment is ultimately dictated by insurance companies. Methods: A retrospective chart review of 52 D+/R− kidney recipients who underwent DAA treatment post‐transplant was performed. Patients were grouped according to their prescription coverage plans, managed by either commercial or government pharmacy benefit managers (PBMs). Results: Thirty‐nine patients had government PBMs and 13 had commercial PBMs. Demographics were similar between the two groups. All patients developed HCV viremia, but cleared the virus after treatment with DAA. Patients with government PBMs were treated earlier compared to those with commercial PBMs (11 days vs 26 days, P = .01). Longer time to DAA initiation resulted in higher peak viral loads ( β = 0.39, R 2 = .15, P = .01) and longer time to HCV viral load clearance ( β = 0.41, R 2 = .17, P = .01). Conclusions: D+/R− transplantation offers patients an alternative strategy to increase access. However, treatment can be profoundly delayed by a third‐party payer authorization process that may be subjecting patients to unnecessary risks and worsened outcomes.